Membership of English sport clubs: A dynamic panel data analysis of the trickle-down effect. Issue 1 (2nd January 2021) - Castellanos-García, Pablo; Kokolakakis, Themis; Shibli, Simon; Downward, Paul; Bingham, Jerry
ABSTRACT: Investments in elite sport and major sporting events are often justified in sport policy by various rationales, one of which is a 'trickle-down' effect whereby successful athletes have a positive impact on general sport participation rates. This effect is likely to be greater when hosting events, as home advantage can contribute to sporting success. The purpose of this research is to explore the possibility of a trickle-down effect on sports club membership in the United Kingdom in the context of the 2012 London Olympic Games. Secondary data were collected on sports club membership levels in 33 sports, over a ten-year period, from 2007–2016 (n = 330). Sporting success was measured by the number of gold medals won in international competitions, the number of major sport events hosted in the UK, and the results of the BBC's Sports Personality of the Year award (SPOTY). The outcomes of a dynamic panel regression analysis show a causal relationship between the trickle-down effect and sports club membership over a four-year period.